How demand for new skills affects wage inequality: The case of software programmers - Gustavo de Souza; Jack Mannion; andJacob Herbstman (Federal Reserve Bank of Chicago, 2024)
We study how the demand for programming skills has impacted inequality. We create a new dataset with information on wages, employment, and software of Brazilian programmers, covering the period from the birth of information technology (IT) to the rise of artificial intelligence (AI). High-ability, high-wage, and highly educated individuals in key technology hubs are more likely to become programmers. Creating software boosts both wages and career prospects of programmers, especially for those with specialized skills in AI and cybersecurity. These wage gains are concentrated among top programmers, increasing inequality within the profession. Therefore, increased demand for specialized skills in programming has contributed to wage inequality both within the programming field and between programmers and other occupations.
Keywords: J24; J23; O33; 330; technological progress; new work; AI; software